The effect of Glycated Haemogloin A1c and Fasting Blood Glucose in Type1 Diabetes (Baghdad Science Journal, 2025)
The glycated haemoglobin A1c(HbA1c) and Fasting blood glucose(FBG) effect on type1 diabetic pateints as a screening tests and as a gold standard for assessing glycemic control in subjects with diabetes were studied . Ninety one blood samples were collected in a peroid between June and the end of November 2012 at AL- Kindy Diabetic Center and Central Child Hospital,48 Females and 43 Males , aging between (11 month- 18 year), are divided into three groups, newly diagnosed , ongoing and healthy control group, with duration of disease between(1 day-3months) and (from birth-8 years) for newly diagnosed and ongoing groups respectevily . The results showed that FBG and HbA1c for newly diagnosed were high (291 mmol/l and 10.6%) respectevily with short duration mean (3.32 week) while ongoing group (207mmol/L and 7.4%) with duration mean(154.5 week) compared with control group values (92.6mmol/L and 4.9%).There was a significant differences between FBG in patients and control at P value < 0.005, and p < 0.05 between HbA1c for patients and control .The correlation of FBG in patients and duration of disease were ( r= - ve 0.19) and for the control group ( r= -ve 0.49 ).When we compared FBG and HbA1c in patient the correlation was (+ve 0.64) .This study concluds that the combined use of FBG and HbA1c are very important for assessing glycemic control and enhanced the detection of diabetes individuals at high risk for diabetes.